Association Between the Normal-Density Psoas Muscle Index and Handgrip Strength or Gait Speed in Maintenance Hemodialysis Patients - Kwack, Byung Hoon; Kim, Jun Chul; Do, Jun Young; Kang, Seok Hui (Frontiers in Medicine, 2021)
Introduction: This study aimed to evaluate the association between the psoas muscle (PM) index with or without fatty infiltration and various indices associated with muscle mass in hemodialysis (HD) patients. Methods: We included stable HD patients (n = 83). The collected data included subjective global assessment (SGA) score, ASM/Ht2 (appendicular muscle mass divided by the squared height in meters), gait speed (GS; m/s), and handgrip strength (HGS; kg). The abdominal CT image was obtained using a CT scanner. The PM and normal-density PM (NPM) indices (mm2/m2) were calculated using the whole PM area or the area with an attenuation range of 35 to 100 HU divided by the squared height in meters. Results: Correlation coefficients for the SGA score, ASM/Ht2, HGS, and GS were greater for the NPM index than for the PM index. The linear regression analysis showed that, on multivariate analysis, the NPM index was significantly associated with the SGA score, ASM/Ht2, and GS. However, the PM index was significantly associated with the SGA score and ASM/Ht2 but not with HGS or GS. For calculating the low GS, the AUROC area was significantly greater for the NPM index than for the PM index (P = 0.012). Conclusion: The present study suggested that the NPM index excluding fatty infiltration may be an early and useful indicator for detecting muscle strength and physical performance among HD patients.